The Bojanov-Naidenov problem for the functions with non-symmetric restrictions on the oldest derivative - Кофанов, Володимир Олександрович (Ukrains’kyi Matematychnyi Zhurnal, 2021)
For given $r \in \NN$, $p, \alpha, \beta, \mu > 0$, we solve theextremal problems$$\int olimits_{a}^{b} x^q_{\pm}(t)dt \to \sup, \;\;\;\; q\ge p,\;$$on the set of pair $(x, I)$ functions $x\in L^r_{\infty}$ andintervals $I=[a,b] \subset \RR$ satisfying the inequalities $ -\beta\le x^{(r)}(t) \le \alpha $ for almost everywhere $t \in \RR $ andthe both of conditions $ L(x_{\pm})_p \leL(\varphi_{\lambda,r}^{\alpha, \beta})_{\pm})_p, $ and such that $\mu \left( {\rm supp}_{[a, b]} x_{+} \right) \le \mu$ or $ \mu\left( {\rm supp}_{[a, b]} x_{-} \right) \le \mu$, where$$ L(x)_p:=\sup\left\{\left\|x \right\|_{L_p[a,b]}: \; a, b \in \RR,\;|x(t)|>0,\;t\in (a, b) \right\},$$$ {\rm supp}_{[a, b]} x_{\pm}:= \{t\in [a, b]: x_{\pm}(t) > 0\} $and $\varphi_{\lambda,r}^{\alpha, \beta}$ is the nonsymmetric$(2\pi/\lambda)$-periodic spline of Euler of order $r$. Inparticular, we solve the same problems for the intermediatederivatives $x^{(k)}_{\pm}$, $k=1,...,r-1$, with $q \ge 1$.